Microelements against the potato phoma - Andriychuk, T.; Skoreyko, A.; MelnykА. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
It is presented the researches results for defeated potato tubers growing and developing the cultivar’s yield on the microelement’s feeding background (boron, copper, manganese). The positive microelement’s impact was shown on their input into the soil during the potato planting and two following nutritions on the saving the affiliated tubers.